(untitled) (Global Journal of Human-Social Science, 2020)
This paper aims at analyzing the socio-economic status of widows in the Jhenidah district and evaluate the impact of socio-economic status on the widows livelihood in society For achieving the purpose of the study the researchers collected the primary data by a structured questionnaire and data were gathered from sixteen respondents from Jhenidah district by a convenient sampling method The researchers in this study found that widows suffer from multiple social problems and restrictions Moreover the widows are feeling discouraged in their lives though they earn a satisfactory figure since dissatisfaction arises from the multiplicity of social problems for the widows